Accelerated Shrinkage of Glaciers in the Altai Mountains From 2000 to 2020 - Chang, Jiawen; Wang, Ninglian; Li, Zhijie; Yang, Daqing (Frontiers in Earth Science, 2022)
Mountain glaciers are an important component of the global hydrological cycle. Existing researches about glacier changes in Altai focused on limited regions. Study about recent glacier changes in the entire Altai Mountains is still lacking. We presented a consistent method for identifying glaciers margins. The two new glacier inventories in 2000 and 2020 were derived from Landsat satellite imagery. Glacier surface elevation change and mass balance was obtained by comparing the 2000 Shuttle Radar Topography Mission (SRTM) and 2020 Digital Elevation Models (DEMs) generated from Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) images. The spatial pattern of glacier changes was discussed in conjunction with climate trends. We mapped a total area of 1096.06±53.32km2 around 2020, which amounts to 1927 glaciers in the Altai Mountains. That was 12.02±3.01% (or 0.60±0.15%·a-1) less than the 1245.75±58.52km2 around 2000. The geodetic mass balance of the monitoring glaciers in Aktru Basin for the period 2000-2011 was used to validate the geodetic survey. The average geodetic mass balance of -0.32±0.09m w.e.·a-1 on monitoring glaciers was slightly exaggerated than the observed mass balance of -0.26m w.e.·a-1, but it was proved that the geodetic mass balance could reflect glacier changes in the Altai Mountains. An average mass loss of 14.55±1.32m w.e. (or 0.74±0.07 m w.e.·a-1) was found during 2000-2020 in the Altai Mountains. Although the glacier area changes and mass balance were characterized by spatial heterogeneity, the glaciers in the Altai had experienced an accelerated shrinkage in 2000-2020 compared to 20th century. The rising temperature is the foremost reason for glacier area shrinkage and mass loss according to the Climatic Research Unit (CRU) reanalysis data.